2019
DOI: 10.1002/lt.25395
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation for Acute‐on‐Chronic Liver Failure

Abstract: Acute-on-chronic liver failure (ACLF) is a syndrome characterized by acute decompensation of previously diagnosed or undiagnosed liver disease with organ failure(s) with high short-term mortality. This study was conducted to report the outcomes of living donor liver transplantation (LDLT) in ACLF and assess the survival benefit of liver transplantation (LT) in these patients. It was a retrospective study of 218 ACLF patients on the basis of European Association for the Study of the Liver (EASL)-chronic liver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…In the ACLF‐3 population, the absence of mechanical ventilation at the time of LT may further improve 1‐year survival probability to approximately 85% . As transplantation markedly improves survival among candidates with ACLF‐3, additional strategies should be considered in caring for this population, including LT after stabilization of organ failures or judicious use of living donor organ transplant …”
Section: Discussionmentioning
confidence: 99%
“…In the ACLF‐3 population, the absence of mechanical ventilation at the time of LT may further improve 1‐year survival probability to approximately 85% . As transplantation markedly improves survival among candidates with ACLF‐3, additional strategies should be considered in caring for this population, including LT after stabilization of organ failures or judicious use of living donor organ transplant …”
Section: Discussionmentioning
confidence: 99%
“…Gustot et al showed a survival rate of 80.9% at 6 months in patients with ACLF 2-3 as compared to 10% in similar grades of ACLF patients who could not undergo LT. The data from our centre 33 published as abstract in international liver transplant society meet 2017 shows survival rate of 80% in transplant recipients as compared to 32% in patients without transplant at 6 months. Artru et al showed survival of 80% in patients with grade 3 ACLF as compared to 7.9% in controls.…”
Section: Lt For Aclfmentioning
confidence: 99%
“…2 Table 3 shows outcome of LT for ACLF. 7,[22][23][24][25][26][27][28][29][30][31][32][33] The majority of studies have shown good outcomes and comparable survival rates in patients transplanted for non-ACLF, however, most of these studies have not included patients with higher ACLF grades (multi-OF). Patients with severe ACLF have been shown to have lower survival rates in some of these studies 30,32 as compared to patients transplanted for non-ACLF, however, even this survival rate is much better than survival of patients without transplantation.…”
Section: Lt For Aclfmentioning
confidence: 99%
“…Yet, it is very likely that very sick patients may not have been added to the LT waitlist. In a study of 218 ACLF patients, fewer patients with ACLF grade 3 re- ceived LT compared to those with ACLF grades 2 or 1 (35%, 72.7%, and 80% for ACLF grade 3, 2, and 1, respectively) [19] . Circulatory and respiratory system failures were higher in the nontransplant group and none of the patients on high support for circulatory and respiratory failure underwent LDLT [19] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 218 ACLF patients, fewer patients with ACLF grade 3 re- ceived LT compared to those with ACLF grades 2 or 1 (35%, 72.7%, and 80% for ACLF grade 3, 2, and 1, respectively) [19] . Circulatory and respiratory system failures were higher in the nontransplant group and none of the patients on high support for circulatory and respiratory failure underwent LDLT [19] . In addition, the dropout rate from waitlists is higher for those with multiple organ failure.…”
Section: Discussionmentioning
confidence: 99%